Evaluation of lumbar spine bracing as a postoperative adjunct to single-level posterior lumbar spine surgery - Sinha, Saurabh; Caplan, Ian; Schuster, James; Piazza, Matthew; Glauser, Gregory; Sharma, Nikhil; Welch, William; Osiemo, Benjamin; Mcclintock, Scott; Ozturk, Ali; Malhotra, Neil (Asian Journal of Neurosurgery, 2020)
Background: Clinical practice in postoperative bracing after posterior single-level lumbar spine fusion (PLF) is inconsistent between providers. This study seeks to assess the effect of bracing on short-term outcomes related to safety, quality of care, and direct costs. Methods: Retrospective cohort analyses of consecutive patients undergoing single-level PLF with or without bracing at a three-hospital urban academic medical center (2013–2017) were undertaken (n = 906). Patient demographics and comorbidities were analyzed. Test of independence, Mann–Whitney–Wilcoxon test, and logistic regression were used to assess differences in length of stay (LOS), discharge disposition/need for postacute care, quality-adjusted life year (QALY), surgical site infection (SSI), hospital cost, total cost, readmission within 30 days, and emergency room (ER) visits within 30 days. Results: Among the study population, 863 patients were braced and 43 were not braced. No difference was seen between the two groups in short-term outcomes from surgery including LOS (P = 0.836), discharge disposition (P = 0.226), readmission (P = 1.000), ER visits (P = 0.281), SSI (P = 1.000), and QALY gain (P = 0.319). However, the braced group incurred a significantly higher direct hospital cost (median increase of 41.43%, P < 0.001) compared to the unbraced cohort (bracing cost excluded). There was no difference in graft type (P = 0.145) or comorbidities (P = 0.20–1.00) such as obesity (P = 1.000), smoking (P = 1.000), chronic obstructive pulmonary disease (P = 1.000), hypertension (P = 0.805), coronary artery disease (P = 1.000), congestive heart failure (P = 1.000), and total number of comorbidities (P = 0.228). Conclusion: Short-term data suggest that removal of bracing from the postoperative regimen for PLF will not result in increased adverse outcomes but will reduce cost.
Keywords: Lumbar fusion; posterior lumbar spine fusion; single-level bracing